The Influence of Price and Product Quality on Brand Switching Behavior of Marcks Loose Face Powder in Banjarmasin - M. Hasanur Arifin; Humaidi Humaidi; Puput Heranika; Setio Utomo (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The aim of this research is to analyze the influence of price and product quality on Brand Switching Behavior of Marcks Loose Face Powder in Banjarmasin City. The specific objectives of this research are 1. Testing the influence of price on Brand Switching Behavior, 2. Analyzing the influence of product quality on Brand Switching Behavior, and 3. Analyzing the influence of price and product quality on Brand Switching Behavior The research method used is a quantitative approach with an explanatory type. The sample in this study was 100 users of Marcks Loose Face Powder. Data were collected using a questionnaire, data analysis was carried out using multiple linear regression analysis using the SmartPLS package computer program. The results of the research show that there is a partial and simultaneous influence of price and product quality on Brand Switching Behavior of Marcks Loose Face Powder in Banjarmasin City Keywords: Price, Product Quality, Brand Switching Behavior